2006
DOI: 10.21897/rmvz.1045
|View full text |Cite
|
Sign up to set email alerts
|

Relaciones talla-peso del barbul (Pimelodus clarias f.c. Bloch, 1785) en la cuenca del Rio Sinu, Colombia

Abstract: Objetivo. Establecer las relaciones de talla y peso del barbul (Pimelodus clarias) en la cuenca del río Sinú. Materiales y Métodos. Se estimaron las relaciones talla-peso de 4324 individuos de Barbul (Pimelodus clarias f.c. Bloch, 1785) colectados entre enero 2000 y diciembre 2002. Resultados. La longitud total (LT) osciló entre 13.0-30.0 cm, promedio de 19.5 (±1.6) cm y el peso total (WT) entre 20.0 y 248.1 g, promedio de 65.8 (±23.2) g. Las relaciones lineales estimadas fueron: LT = 1.92 (± 0.16) + 1.20 (± 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…both hybrids was close to 1.00 (r = 0.998), which demonstrated a strong relationship between these two variables. In addition, the value of the growth coefficient (b) obtained suggests that the growth was isometric (SANTOS-SANES et al, 2006), similar to that reported by PRADA (1982) in C. macropomum. Other experiments using higher stocking densities described minor allometric growth: PASQUIER et al (2011) reported 2.3 (r = 0.96) for C. macropomum raised in cages and an experiment in tanks obtained values of 2.7-2.93 for cachamoto (BAUTISTA et al, 2005), while for P. brachypomus POLEO et al (2011) reported values of 3.4379 (r 2 = 0.9517) and 3.5843 (r 2 = 0.9823).…”
Section: Discussionsupporting
confidence: 89%
“…both hybrids was close to 1.00 (r = 0.998), which demonstrated a strong relationship between these two variables. In addition, the value of the growth coefficient (b) obtained suggests that the growth was isometric (SANTOS-SANES et al, 2006), similar to that reported by PRADA (1982) in C. macropomum. Other experiments using higher stocking densities described minor allometric growth: PASQUIER et al (2011) reported 2.3 (r = 0.96) for C. macropomum raised in cages and an experiment in tanks obtained values of 2.7-2.93 for cachamoto (BAUTISTA et al, 2005), while for P. brachypomus POLEO et al (2011) reported values of 3.4379 (r 2 = 0.9517) and 3.5843 (r 2 = 0.9823).…”
Section: Discussionsupporting
confidence: 89%